Prognostic incremental role of right ventricular function in acute decompensation of advanced chronic heart failure. (16th March 2016) - Frea, Simone; Pidello, Stefano; Bovolo, Virginia; Iacovino, Cristina; Franco, Erica; Pinneri, Francesco; Galluzzo, Alessandro; Volpe, Alessandra; Visconti, Massimiliano; Peirone, Andrea; Morello, Mara; Bergerone, Serena; et al.
Abstract: Aims: The purpose of this study was to evaluate the additional prognostic value of echocardiography in acute decompensation of advanced chronic heart failure (CHF), focusing on right ventricular (RV) dysfunction and its interaction with loading conditions. Few data are available on the prognostic role of echocardiography in acute HF and on the significance of pulmonary hypertension in patients with severe RV failure. Methods and results: A total of 265 NYHA IV patients admitted for acute decompensation of advanced CHF (EF 22 ± 7%, systolic blood pressure 107 ± 20 mmHg) were prospectively enrolled. Fifty‐nine patients met the primary composite endpoint of cardiac death, urgent heart transplantation, and urgent mechanical circulatory support implantation at 90 days. Pulmonary hypertension failed to predict events, while patients with a low transtricuspid systolic gradient (TR gradient <20 mmHg) showed a worse outcome [hazard ratio (HR) 2.37, 95% confidence interval (CI) 1.12–5.00, P = 0.02]. RV dysfunction [tricuspid annular plane systolic excursion (TAPSE) ≤14 mm] in the presence of a low TR gradient identified patients at higher risk of events (HR 2.97, 95% CI 1.19–7.41, P = 0.02). Multivariate analysis showed as best predictors of outcome low RV contraction pressure index (RVCPI), defined as TAPSE × TR gradient, and high estimated right atrial pressure (eRAP). Adding RVCPI (<400 mm*mmHg) and eRAP (≥20 mmHg) to conventional clinical (ADHERE risk tree and NT‐proBNP) and echocardiographic risk evaluation resulted in an increase in net reclassification improvement of +19.1% and +20.1%, respectively ( P = 0.01) and in c‐statistic from 0.59 to 0.73 ( P < 0.01). Conclusions: In acute decompensation of advanced CHF, pulmonary hypertension failed to predict events. The in‐hospital and short‐term prognosis can be better predicted by eRAP and RVCPI.